Psychological Impacts On Adolescent Victims Of Bullying: Phenomenology Study - Laili Nur Hidayati; Rizky Amalia (Universitas Muhammadiyah Semarang, 2021)
One of the frequent cases of violence against adolescents in the school environment is bullying. The incidence of bullying is increasing every year. This has had an impact. Based on KPAI data, there were 37,381 incidents of bullying in Indonesia from 2011 to 2019 which commonly occur in school environments. Research conducted by non-governmental organizations explained that the biggest bullying phenomenon occurred in three cities in Indonesia, namely Yogyakarta (77.5%), Surabaya (59.8%), and Jakarta (61.1%). The incidence of bullying is increasing every year and has an adverse impact or effect on both the perpetrator and the victim. The purpose of this study was to determine the psychological impact that arises on adolescents who are victims of bullying. This study uses a qualitative approach, namely a phenomenological approach. Data collection was carried out through in-depth interviews, the number of participants in this study was 12 people, including students aged between 12 and 15 years and was determined through purposive sampling. Data analysis in this study used open code 4.02. The results showed that some of the participants experienced severe psychological impacts. Some of them feel hopeless, feel inferior, and some hurt themselves. The conclusion of this study found that the incidence of bullying in adolescents has a negative impact on bullying victims who need care from school and parents.